The Influence of Social Media on Self-Medication and Treatment of Acne Vulgaris - Butar Butar, Agatha Uli Angelica; Paramita, Deryne Anggia; Putri Amelia; Panggabean, Yoan Carolina (Faculty of Medicine, Universitas Airlangga, 2025)
Background: With the advancement of technology, access to information about acne vulgaris has become easier. Social media has become a key platform for influencers and doctors to educate the public about acne, which often leads acne sufferers to use social media as a reference for understanding the condition and treatment options. As a result, many individuals choose to practice self-medication based on information obtained from social media. Purpose: This study aims to examine the impact of social media on self-medication and the treatment of acne vulgaris. Methods: This is an analytical cross-sectional study conducted among high school students. The sample was selected using consecutive sampling. Data was collected through a questionnaire that assessed social media usage, self-medication practices, and treatment outcomes. Result: Among the 92 respondents who participated in this study, the following results were found: 18 respondents had a high level of social media usage, 54 respondents had a moderate level, and 20 respondents had a low level. In addition, 64 respondents expressed interest in self-medication, while 28 respondents were not interested in self-medication. The results of the acne treatment of 64 people interested in self-medication showed that eight people had significant improvement in self-medication results, 52 people had slight improvement, and four people had no improvement. The bivariate analysis shows that social media influences self-medication but does not affect treatment outcomes. Conclusion: Social media influences self-medication but does not affect the treatment outcomes of acne vulgaris.